ESPRESSO: A novel device for laser-assisted surgery of the anterior eye segment. Issue 2 (3rd March 2016) - Russo, Sheila; Petroni, Gianluigi; Quaglia, Claudio; Niccolini, Marta; Rossi, Francesca; Menabuoni, Luca; Pini, Roberto; Fortuna, Damiano; Dario, Paolo; Menciassi, Arianna
Abstract: Introduction: Merging robotics with laser eye surgery could enhance precision, repeatability and automation. During some eye laser procedures the patient is awake, thus eye stabilization is desired to avoid movements that could affect the treatment.Material and methods: The ESPRESSO platform has a two-stage actuation system to position a stabilization tool on the eye, a proximity sensing unit to monitor the stabilization tool position, and a sensing unit to monitor the pressure exerted on the eye. The platform is tested in-vitro and ex-vivo with clinicians. A maximum pressure to be exerted on the eye is defined with expert ophthalmic surgeons to be 22 mmHg: physiological intraocular pressure (IOP) range is 10-21 mmHg. This pressure corresponds to a force of 0.3 N.Results: The necessary contact force to have eye fixation (according to the clinicians' feedback) is evaluated: maximum values resulted always below 0.3 N. A maximum IOP increase of 4.67 mmHg is observed, that is a slight variation with respect to the performance of other platforms (IOP elevations up to 328 mmHg).Conclusion: Design and initial assessment of the platform is presented. Eye stabilization is performed without exceeding the critical contact force value and causing large/sudden IOP increases.